What can earnings calls tell us about the output gap and inflation in Canada? - Marc-André Gosselin; Temel Taskin (Bank of Canada, 2023)
We construct new indicators of the imbalance between demand and supply for the Canadian economy by using natural language processing techniques to analyze earnings calls of publicly listed firms. The results show that the text-based indicators are highly correlated with official inflation data and estimates of the output gap and improve the accuracy of inflation forecasts. This suggests that these indicators could help central banks foresee inflationary pressures in the economy. Our examination of other topics in earnings calls, such as supply chain disruptions and capacity constraints, points to the potential benefits of using textual data to quickly draw insights on a range of relevant topics. We conclude that text-based measures of economic slack should be included in central banks' monitoring and forecasting toolkits.
Keywords: C1; C3; E3; E5; 330; Central bank research; Domestic demand and components; Econometric and statisticalmethods; Inflation and prices; Potential output